Menopausal syndrome: clinical presentation and management - Patil, Sunil Somnath; Sambarey, Pradip Wamanrao; Patil, Chandrakala Sunil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Menopause is physiological stage in woman’s life. Although most of women accept them, some do have a disturbed life due to various symptoms, mostly because of estrogen deprivation. Methods: This is a prospective clinical study of 200 menopausal women attending the gynaecology OPD or admitted in the wards with various symptoms as well as some gynaecological problems. Young women with surgically induced menopause and women with psychiatric disorders were excluded. Results: The duration between menopause and appearance of symptoms varied from 1yr to 10 yrs. The average age of menopause in our study was 46.5 yrs. Vasomotor symptoms (65%) were common followed by psychosomatic symptoms (62%), vaginal dryness (45%) and urinary symptoms (40%). Stress, irritability, sleep problem, weight gain were some of common presentations to OPD. Urinary incontinence and atrophic vaginitis were also seen predominantly. The management consists mainly of counseling and life style modification, exercise, yoga meditation etc. Some of the women required estrogen cream, 70 women required surgical treatment. Overall the response to various medications was satisfactory and on follow up the symptoms was found to be much less. Conclusions: There is need of setting menopausal clinics and centres to help women with symptoms and signs of estrogen deprivation. Counseling and education are main treatment modalities.